The Delphi study in media literacy (MEDLIT) Erasmus+ project: lessons learnt - Rosya Izyanie Shamshudeen; Nik Maheran Nik Muhammad; Sabariah Mohamed Salleh; Mokhtarrudin Ahmad; Wan Anita Wan Abas (Penerbit Universiti Kebangsaan Malaysia, 2023)
The procedure and practice in conducting a study on media literacy education intervention need to be clarified to guide quality research. In recent years, only limited Delphi studies have been conducted in the Malaysian context. Despite recognizing the influence of socio-cultural settings on the conduct of any research, empirical literature on the best and most suitable means to conduct Delphi studies within the Malaysian socio-cultural context has not grown in proportion to the evolution of Delphi method application in local social-science studies. This article establishes methodological considerations in employing the Delphi method by investigating issues relating to data source, instrument, data collection procedures and management in the implementation in designing and conducting a successful Delphi study in the Malaysian socio-cultural context. The reflection of Delphi method in identifying media literacy knowledge that is deemed to be important for inclusion in an introductory media literacy Massive Open Online Course (MOOC) will be explored. This study demonstrates a novel and inclusive strategy that might be used in Southeast Asian nations. Our study suggested appropriate strategies in order to develop and carry out more feasible Delphi studies. New researchers should take into consideration the numerous issues and difficulties identified in this study. The main contribution of this study is a set of dependable and useful guidelines that may be used to design and carry out future Delphi studies that include the study's reasoning, justification of its advantages, the official logo of the institutions the researchers are affiliated with, and authorization from the funding organisations, which may add weightage to the study's significance.